Village Education Committees in Uttar Pradesh: Structure and Member Profile - Tripathi, Krishna Kant (JOURNAL OF INDIAN EDUCATION, 2012)
Decentralised management of education through community participation and community mobilisation is conceived to be essential for successful and effective management of elementary education. Policy of decentralisation in India at the grass-root level has institutionally metamorphosed in the formation of Village Education Committees (VEC). Structure of VEC and profile of its members give a glimpse of the nature and level of community participation. Therefore, every state government including UP (Uttar Pradesh) has prescribed the structure of VEC through GO/ordinance/statutes. This study presents the structure of VEC and the profile of its members in UP In UP, at some places VECs are formed against the norms. Low education of the members of VEC, no timely reorganisation of VEC and absence of VEC members’ wards from VEC managed school denotes passive or no participation of community in educational management.